2017
DOI: 10.1515/sjecr-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Depression and Proactive Coping in Underground Coal Miners in Serbia - Pilot Project

Abstract: Mining is unsurprisingly considered a high-risk occupation because it involves continuous hard labour under highly demanding and stressful conditions. Many of these work stressors can impair individuals' well-being in both a physiological and psychological sense. Th e aims of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In Serbia, burnout was examined among recruiters in human resource services of different companies [ 44 ], students of the University of Belgrade [ 45 , 46 , 47 ], special education professionals [ 48 , 49 ], social workers [ 50 ], pharmacists [ 51 ], professionals in the pharmaceutical manufacturing industry and marketing [ 52 , 53 ], underground coal miners [ 54 ], formal caregivers of children with cerebral palsy [ 55 ], workers in the food industry [ 56 ], and the most common among healthcare professionals [ 57 , 58 , 59 , 60 ]. The majority of these studies examined burnout using the Maslach Burnout Inventory.…”
Section: Introductionmentioning
confidence: 99%
“…In Serbia, burnout was examined among recruiters in human resource services of different companies [ 44 ], students of the University of Belgrade [ 45 , 46 , 47 ], special education professionals [ 48 , 49 ], social workers [ 50 ], pharmacists [ 51 ], professionals in the pharmaceutical manufacturing industry and marketing [ 52 , 53 ], underground coal miners [ 54 ], formal caregivers of children with cerebral palsy [ 55 ], workers in the food industry [ 56 ], and the most common among healthcare professionals [ 57 , 58 , 59 , 60 ]. The majority of these studies examined burnout using the Maslach Burnout Inventory.…”
Section: Introductionmentioning
confidence: 99%
“…Other samples of the theme are the studies of Corral et al 40 ) , Liu & Chen 41 ) , Manic et al 42 ) and Joaquim et al 43 ) The first one approached on neurological and neuropsychological deterioration due to the mercury exposure. They used the neurological examination and neuropsychological evaluation of depressive symptoms with BDI-II scale, auditive, visual memory, visoconstruction and visuoperception with REY complex figure and executive functions with WCST.…”
Section: Resultsmentioning
confidence: 99%
“…The studies conducted on samples of university students found that proactive coping was positively correlated with hope, a sense of life and life satisfaction (Ranđelović & Minić, 2012;Stanojević et al, 2014), and social support (Stanojević et al, 2014). Negative correlations, on the other hand, were obtained with depression in a sample of students (Manić et al, 2017) and university students (Stanojević et al, 2014).…”
Section: Introductionmentioning
confidence: 99%